2019
DOI: 10.1042/bsr20181665
|View full text |Cite
|
Sign up to set email alerts
|

Modified lipoproteins in periodontitis: a link to cardiovascular disease?

Abstract: There is a strong association between periodontal disease and atherosclerotic cardiovascular disorders. A key event in the development of atherosclerosis is accumulation of modified lipoproteins within the arterial wall. We hypothesise that patients with periodontitis have an altered lipoprotein profile towards an atherogenic form. Therefore, the present study aims at identifying modifications of plasma lipoproteins in periodontitis. Lipoproteins from ten female patients with periodontitis and gender- and age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 72 publications
0
19
0
2
Order By: Relevance
“…Serum Paraoxonase/Arylesterase 1 (PON1) activity was measured in plasma as previously described [ 28 ]. Briefly, lithium heparin plasma was diluted 1:80 with a salt buffer (20 mM Tris–HCl and 1.0 mM CaCl 2 ) and a triplicate of 20 μl diluted plasma were added to the wells in a UV-transparent 96-well plate (Sigma–Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Serum Paraoxonase/Arylesterase 1 (PON1) activity was measured in plasma as previously described [ 28 ]. Briefly, lithium heparin plasma was diluted 1:80 with a salt buffer (20 mM Tris–HCl and 1.0 mM CaCl 2 ) and a triplicate of 20 μl diluted plasma were added to the wells in a UV-transparent 96-well plate (Sigma–Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Also crosssectional studies have reported that vitamin D deficiency is associated with increased risk of CVD and mortality [19,20]. Elevations of serum lipids and low serum levels of 25-hydroxyvitamin D may have a serious negative impact on periodontal and cardiovascular health [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Both APOA1 and APOA2 were found to be significantly downregulated in G1–C and G1–G2 comparisons. While their role in periodontitis is recently investigated [ 51 ], their possible association with caries susceptibility has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%